Dynamic Thermal Study of a Building Insulated with Local Biosource Materials and Analysis of Consumption - SEMASSOU, GUY CLARENCE; VODOUNNOU, Edmond (My University, 2021)
The quality of infrastructure, including buildings, is an indicator of a country's development status. However, it must be noted that these buildings entail high energy costs and also contribute to the global greenhouse effect. The building sector is therefore a crucial issue in terms of adapting to climate change because it is at the heart of a dual energy and environmental problem. To address this challenge, energy efficiency policies are increasingly being adopted worldwide, with the aim of improving the energy performance of buildings. In the present work, the thermo-physical properties of four types of materials, namely: "cement and roast fibre" composite, "cement and rice husk" composite, "agglomerate" and "cement and bar soil" composite, were exploited to implement thermal simulations under TRNSYS environment. The aim was to determine the thermal contributions of the walls built with these materials and those allowing a better comfort in the building by estimating and comparing the energy needs of the proposed variants with those of the reference building. The study showed that the walls made of "cement and rice husks" composite and "cement and roast tree fibres" composite allow to reduce respectively by 20% and 11%, the cooling needs linked to air conditioning for the living room, and respectively by 32% and 27% for the bedroom, compared to the reference building made of agglomerate (with a thickness e= 0.15 m). For the walls made of "cement and earth bar", the cooling requirement increased by 31% for the living room and decreased by 5% for the bedroom, compared to the "chipboard" reference building. Furthermore, the TEWI evaluation showed that the "cement and rice husk" and "cement and roast fibre" composites have a lower environmental impact.
Keywords: Thermal Insulation; Roast Wood Fibres; Rice Husks; Chipboard; Bar Soil; Dynamic Thermal Simulation